Class II malocclusion treatment with the Herbst appliance in patients after the growth peak - José Carlos de Castro Alvares; Rodrigo Hermont Cançado; Fabrício Pinelli Valarelli; Karina Maria Salvatore de Freitas; Christian Zamberlan Angheben (Dental Press Editora, 2013)
OBJECTIVE: The objective of this study was to evaluate dentoskeletal effects in the treatment of Class II malocclusion performed with the Herbst appliance in patients at post-peak stage of growth. METHODS: The sample consisted of 16 patients with Class II malocclusion and average initial and final ages of 14.04 (ranging from 11.50 to 35.66) and 17.14 (ranging from 13.68 to 38.64) years, respectively, who were treated for an mean time of 2.52 years. Lateral cephalograms were obtained at treatment onset (T1) and completion (T2) to evaluate the effects of therapy. Initial dental casts were also used to evaluate the overjet and the anteroposterior severity of molar relationship at treatment onset. The cephalometric changes between initial and final stages were compared by means of the non-parametric Wilcoxon test. RESULTS: The results showed that the Herbst appliance did not promote significant changes in the maxillary component and the effective length of the mandible significantly increased without improving the maxillomandibular relationship. Changes in the maxillary and mandibular dentoalveolar components revealed that the maxillary incisors exhibited retrusion and lingual tipping, while the mandibular incisors presented increased protrusion and buccal tipping. The dental relationships exhibited significant improvements with the treatment. CONCLUSION: Based on the present results, it was concluded that the effects of treatment performed with the Herbst appliance in patients at post-peak stage of growth are predominantly of dentoalveolar nature.